(untitled) (Al-Academy, 2025)
This study explores the relationship between the artist and honeybees as a plastic and aesthetic medium in contemporary arts, focusing on the utilization of bees and their products—such as beeswax, honey, and propolis—in creating artistic works that reflect the aesthetics of nature and carry environmental and cultural dimensions. The study adopts a descriptive-analytical approach to examine the experiences of contemporary artists who have incorporated bees as a creative element, aiming to highlight the relationship between humans and nature while showcasing the potential of employing bee products as sustainable artistic materials that foster innovation. Furthermore, the study discusses the role of bees in visual arts as a symbol of environmental cooperation and artistic creativity, emphasizing their significance in enhancing environmental awareness and using art as a means to address contemporary environmental and social issues. The study is based on the hypothesis that integrating honeybees and their products as an artistic medium contributes to the evolution of artistic practices, enabling artists to adopt new techniques and mediums that produce expressive visual formations, thereby expanding the possibilities of environmental and experimental art. To achieve its objectives, the study relies on a descriptive-analytical methodology, studying the relationship between artists and honeybees in contemporary art, analyzing key materials derived from bee products, and reviewing the experiences of artists who have employed bees and their derivatives as sculptural and artistic tools within their works